Analisis Pertimbangan Hakim dalam Putusan No.0253/Pdt.P/2016/Pa.Pbg Tentang Dispensasi Pernikahan - Mutakin, Ali; Marwati, Lusi (STAINI Press, 2022)
Marriage dispensation is the granting of the right by the Religious Courts to a person to marry even though they have not reached the minimum age for marriage, if the situation